2022
DOI: 10.3390/ijms23179984
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Novel Soil Amendment Based on Biomass Fly Ash Encapsulated in Calcium Alginate Microspheres

Abstract: Biomass fly ash (BFA) from a biomass cogeneration plant was encapsulated into calcium alginate microspheres (ALG/Ca) and characterized. An FTIR analysis indicated that BFA loading weakened molecular interactions between ALG/Ca constituents (mainly hydrogen bonding and electrostatic interactions), thus changing the crosslinking density. SEM and AFM analyses revealed a wrinkled and rough surface with elongated and distorted granules. The in vitro release of BFA’s main components (K, Ca, and Mg) was controlled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Chitosan (CS) is a polymer derived from chitin and is considered a very versatile, biocompatible, biodegradable, and non-toxic biomaterial. It has mucoadhesive properties, facilitating the transport of bioactive compounds across the cell membranes, which implies a great potential for use in the agroindustry [ 22 , 23 ]. Moreover, CS can elicit plant defense responses against stress and has biostimulant characteristics [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan (CS) is a polymer derived from chitin and is considered a very versatile, biocompatible, biodegradable, and non-toxic biomaterial. It has mucoadhesive properties, facilitating the transport of bioactive compounds across the cell membranes, which implies a great potential for use in the agroindustry [ 22 , 23 ]. Moreover, CS can elicit plant defense responses against stress and has biostimulant characteristics [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…These materials have the potential to improve the transportation, storage, and delivery efficiency of sustainable nutrients to plants. 66 Similarly, another study by van der Merwe et al (2022) also showed promising results for alginate microparticles within the soil as a fertiliser release agent, and a pH controlling agent with the inclusion of limestone. 67…”
Section: Polymer Selection For Agricultural Sapsmentioning
confidence: 93%
“…Other studies on calcium alginate microparticles in this application, such as the one conducted by Vinceković et al (2022), which utilised biomass fly ash, indicate this is a promising area for research. These materials have the potential to improve the transportation, storage, and delivery efficiency of sustainable nutrients to plants.…”
Section: Soil Amendmentmentioning
confidence: 99%
“…In materials science, this technology reduces the size of the synthesized material and improves the surface potential, porosity, dispersivity, surface area, and surface functional groups of many modern materials [12]. These properties make them smart materials, which are utilized for the targeted transport of nutrient or pesticides [12,13], improving the nutrient utilization efficiency of conventional or modern fertilizers [9,14] and solving nutrient loss problems in agriculture [15,16]. Therefore, nanotechnology has the potential to synthesize materials that are suitable for reducing environmental losses from conventional fertilizers (organic or synthetic chemicals), such as FM.…”
Section: Introductionmentioning
confidence: 99%